The cultivation of affective intelligence. (Journal of Parents and Teachers, 2014)
The term "emotional intelligence" has become more prominent. This article emphasizes the importance of working the link that exists between cognitive and affective processes to know the behavior of the human being. Affective education is also essential in schools.
Keywords: Emotional intelligence; affectivity; affective education.